Latin American sociology as mere sociology: Bourdieusian reflexivity as a meeting point - Sandoval Aragón, Sergio Lorenzo (2026)
A discussion of the potentialities and limitations of Pierre Bourdieu's sociology in Latin America can be based on «reflexivity,» which is its most defining characteristic and which he conceived as the absolute condition of possibility and autonomy of sociological knowledge. Reflexivity is the use of the theoretical and empirical acquisitions of sociology itself to think about its conditions of possibility and control its possible biases (for example, Eurocentrism). Having emerged from a radical critique of an anthropology complicit with colonialist power, a critique that later extended to other forms of domination and other contexts, Pierre Bourdieu's sociology has contributed and can continue to contribute to Latin American sociology not only with its theories and methodological innovations, but mainly because the reflexivity it proposes opens up a space for rational communication, where a critical dialogue from the knowledge of the Global South can be established.